Stimulasi Laser sebagai Alternatif untuk Induksi Estrus pada Kambing Bligon (Laser Stimulation as an Alternative for Estrus Induction on Bligon Goats) - Sigit Bintara (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
Reproduction is a very important factor in maintaining livestock productivity. For better reproductivity, estrus induction is one of very important ways to be performed. Estrus induction is usually performed with hormonal method,such as application of PGF2α, but the disadvantage is that it is relatively expensive. For this reason, it is necessary to promote technological breakthrough to lower cost of estrus induction. The aim of this study was to know whether laserstimulation on the points of reproductive acupuncture could be performed for estrus induction on Bligon goats, as it is usually performed with hormonal method. Fourteen female Bligon goats aged 2 years old were randomly divided into two groups, each group consisted of 7 goats. Group I was stimulated with laser and group II was injected with 1.25 mg per head of PGF2α. Laser stimulation was conducted for 10 seconds on each point of acupuncture on day 1, 2, and 3, and was repeated on day 11, 12, and 13. PGF2α injection was performed on day 1 and was repeated on day 11. The observed variables were the percentage of estrus, onset of estrus, estrus duration and progesterone level when estrus occurred after the second estrus induction. The results of the study showed that laser stimulation for estrus induction did not indicate significant difference compared to PGF2α injection, in terms of the percentage of goats undergoingestrus, onset of estrus and the estrus duration. It was concluded that laser stimulation could be used for estrus induction on Bligon goats.(Key words: Laser, Estrus induction, Bligon goats)